Outcomes of medical treatment for accommodative impairments, with a consideration of the balance of autonomic innervation and pupillography data - Dukhayer Shakir; N.M. Bushuieva; S.B. Slobodianyk (Journal of Ophthalmology, 2018)
Background: The relationships of characteristics of accommodation-and-convergence pupil response with age and balance between sympathetic and parasympathetic innervation (or eutony) in healthy children and adolescents are complex and ambiguous. The results of this study were needed to select a treatment for accommodative impairments.